The rules of success : how managers can overcome setbacks and grow - Drath, Karsten (Routledge, 2019)
"This book is about the rules of long-term professional success. The international study on which this book is based suggests that success is, above all, one thing: the quest for a combination of happiness and satisfaction, coupled with economic independence. However, the data also suggest that the definition of success varies significantly from person to person. And furthermore, it seems like success is not an objective quality, but at least partly it results from a process of comparison with a peer group - which means in turn that the selection of your peer group is crucial for your perceived level of success in life. The author argues that, in fact, certain success factors do exist and that they are fewer in number than one might think. But above all, if we look thoroughly at the lives of truly successful people, it soon becomes apparent that success primarily has to do with overcoming setbacks, failure and crisis. This ability to effectively process adversity is also known as resilience. Because of its criticality for success this concept is discussed in greater depth using the FiRE model (Factors improving Resilience Effectiveness) as a structure. This concept has been developed by the author through many years of research. It differs from existing models due to its holistic approach including analysing different disciplines of science such as biology, medicine, brain research, epigenetics, sociology, psycho-neuro-immunology etc